2021
DOI: 10.3390/su13052836
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Energy-Efficient Evaporative Cooling Systems for Poultry Farm Application in Multan (Pakistan)

Abstract: Poultry are one of the most vulnerable species of its kind once the temperature-humidity nexus is explored. This is so because the broilers lack sweat glands as compared to humans and undergo panting process to mitigate their latent heat (moisture produced in the body) in the air. As a result, moisture production inside poultry house needs to be maintained to avoid any serious health and welfare complications. Several strategies such as compressor-based air-conditioning systems have been implemented worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Additionally, while the air temperatures were low (22.16–22.88 °C) near the pads, they gradually increased by almost 2.50 °C from the pads to the exhaust fans ( Figure 8 a,b). Numerous studies have revealed that evaporative cooling pad systems may provide a solution for controlling the high temperatures that negatively affect the poultry buildings [ 51 , 52 , 53 ]. However, although the evaporative cooling pad system significantly decreases indoor temperatures, it also causes a significant increase in relative humidity inside the house ( Figure 8 c,d), which can be problematic, especially in humid climates [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, while the air temperatures were low (22.16–22.88 °C) near the pads, they gradually increased by almost 2.50 °C from the pads to the exhaust fans ( Figure 8 a,b). Numerous studies have revealed that evaporative cooling pad systems may provide a solution for controlling the high temperatures that negatively affect the poultry buildings [ 51 , 52 , 53 ]. However, although the evaporative cooling pad system significantly decreases indoor temperatures, it also causes a significant increase in relative humidity inside the house ( Figure 8 c,d), which can be problematic, especially in humid climates [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Authors have extensively studied desiccant air-conditioning options for the next generation greenhouse air-conditioning in literature [1,3,4,14,[32][33][34][35]. Ashraf et al [33] studied silica-gel desiccant dehumidification based Maisotsenko cycle evaporative cooling system for the next generation agricultural greenhouse.…”
Section: Desiccant Air-conditioning For Greenhouse Temperature/humidity Controlmentioning
confidence: 99%
“…To guarantee a proper indoor climate, the air temperature, moisture and air quality must be controlled by ventilation, heating, cooling, etc. [ 9 ]. However, these control methods represent a considerable share of the total energy consumption of poultry farming.…”
Section: Introductionmentioning
confidence: 99%